A CRITICAL DISCOURSE ANALYSIS OF HILLARY CLINTON’S SPEECH “WOMEN’S RIGHTS ARE HUMAN RIGHTS” - Quyen, Pham Thi (VNU Journal of Foreign Studies; Vol 38 No 5DO - 10.25073/2525-2445/vnufs.4794, 2022)
In the research, the speech “Women’s rights are human rights” by Hillary Clinton will be analyzed in the light of critical discourse analysis (CDA) as both theory and method to reveal how power and ideology are embedded in language in particular and the relation between language and society in general. Initially, the theoretical framework of CDA, the concepts of power and ideology are presented. The social context of women’s position including women’s position in the past and women’s position nowadays is also revealed. The research then briefs on Hillary Clinton’s role in struggling for women’s rights. In terms of methodology, the importance of Systemic Functional Grammar to CDA and a framework of CDA procedure, which set the basis for the analysis of the speech “Women’s rights are human rights”, will be introduced and explained. Thirdly, the article analyzes the speech in the light of CDA. The analysis consists of three stages namely description, interpretation and explanation. The last part summarizes the major findings, provides concluding remarks, gives implication to teaching and learning translation and makes recommendations for further studies.